Responding to health information technology reported safety events: Insights from patient safety event reports. Issue 3 (June 2019) - Adams, Katharine T; Kim, Tracy C; Fong, Allan; Howe, Jessica L; Kellogg, Kathryn M; Ratwani, Raj M
Objective: We analyzed the described resolutions of patient safety event reports related to health information technology to determine how healthcare systems responded to these events, recognizing that certain types of solutions such as training and education have a limited impact. Methods: A large database of over 1.7 million patient safety event reports was filtered to include those identified by the reporter as being related to health information technology. The resolution text was manually reviewed and coded into one or more of four categories: No Resolution, Training/Education, Policy, Information Technology-oriented solution. Results: Most events (64%) did not include a resolution. Of those that did, Training/Education was the most commonly reported single or component of a multi-pronged solution (55%), followed by Information Technology (45%). Only 59 events (6% of resolutions) described more than one method of resolution. Conclusion: Health information technology-related patient safety event resolutions most often described a solution that suggested additional training or education for healthcare staff, despite the recognized limitations of training and education in resolving these events. Few events suggested multiple resolution methods. Ensuring health information technology-related events are resolved and incorporate effective solutions should be a continued focus area for healthcare systems.